PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN KOPERASI NUSA TAWANG REJO BELITANG OGAN KOMERING ULU TIMUR - Tata Suberkah, Bayu; Harlofida, Demsie (Jurnal Trisna Riset, 2024)
The Nusa Tawang Rejo Belitang Ogan Komering Ulu Timur Cooperative is a branch of the Nusa Raya Cipta cooperative which is based in Kelapa Gading, North Jakarta. This cooperative is one of the savings and credit cooperative financial institutions which operates in the field of credit or providing loans guaranteed by BPKB motorbikes or cars, seeking to improve the performance of its employees through implementing a good leadership style. Based on this, the problem faced is how leadership influences employee performance. This research aims to analyze the influence of leadership style on employee performance at the Nusa Tawang Rejo Belitang Ogan Komering Ulu Timur Cooperative. Data collection techniques used in this research include interviews, observation, documentation, questionnaires and literature study. The calculation results show that there is a very strong relationship between leadership style and employee performance, an r number is obtained with a correlation value of 0.8633. Then the hypothesis test proves that leadership style has a significant effect on employee performance as seen in (t count = 3.421 > t table = 2.132). In conclusion, implementing an effective leadership style contributes to increasing employee productivity and performance. Therefore, it is recommended that leaders pay attention to employee conditions and carry out regular performance evaluations to improve work efficiency and effectiveness.